We're going on a bear hunt - Rosen, Michael (Walker Entertainment London, 1993)
"We're Going on a Bear Hunt" is a fun, rhythmic story about a family$1 (Bs adventure through various landscapes as they search for a bear. Along the way, they overcome challenges and obstacles, teaching the importance of persistence and teamwork.s